Production of tropical oyster seed in hatchery - Mohd, Noor Fakhrina; Christianus, Annie; Ehteshami, Fariborz (Green Wave publishing of Canada, 2018)
Oysters have been collected from wild since long time ago for human consumption. Recent development in aquaculture has allows the production of its seed in hatchery. Factors favoring the oyster production are stocking density, water quality and the availability of live food. These factors can increase the growth and survival of the oyster. Fundamental knowledge on life cycle and biology of oyster is important as it can become the basis for successful development of oyster culture. Due to the limited seed supply, hatchery produce seedlings are important to support the development of oyster industry.